A 'turn‐on' fluorescent chemosensor for quantification of serum albumin in aqueous solution at neutral pH. (10th November 2015) - Li, Yuanyuan; Li, Kai; He, Juan
Abstract: A fluorescent chemosensor 1 (4‐diethylamino‐2′‐hydroxychalcone) for detecting serum albumin with long‐wavelength emission, good selectivity and facile synthesis was reported. Upon the addition of bovine serum albumin (BSA) to an aqueous solution of 1 at neutral pH, a 'turn‐on' fluorescence response was observed at 596 nm based on a hydrophobic binding mode between 1 and BSA. A linear range of 0.10–1.00 mg/mL and a detection limit of 9.1 µg/mL for BSA were obtained, respectively. Moreover, 1 was successfully applied to detect BSA in real bovine serum samples with satisfied recovery and accuracy, which suggested that 1 could serve as a valid and effective fluorescent chemosensor for quantification of BSA. Copyright © 2015 John Wiley & Sons, Ltd.